Being mindful of perfectionism and performance among collegiate gymnasts: A person-centered approach - Van Dyke, E. D.; Metzger, A.; Zizzi, S. J. (Journal of Clinical Sport Psychology, 2021)
Little research has integrated mindfulness and perfectionism, particularly within sports wherein athletes are judged on performance to a standard of perfection. The current study had two primary aims: (a) to explore profiles of mindfulness and perfectionism among intercollegiate gymnasts through a person-centered approach and (b) to analyze differences in objective performance across the resulting profiles. The analytic sample consisted of 244 NCAA gymnasts who completed self-report measures of mindfulness and perfectionism. Competitive performance records (i.e., national qualifying scores) were then gathered for participating gymnasts. Cluster analyses revealed a three-cluster solution; however, significant performance differences were not observed across the three profiles due to lower than desired power. Small to moderate effect size estimates provided some evidence that perfectionism may be adaptive to gymnastics performance. Elite-level athletes were represented across three distinct profiles, suggesting that more than one profile of characteristics may be adaptive for reaching high levels of performance.